Pengetahuan Ibu-Ibu tentang Tes IVA - Tedy Candra Lesmana (DIMAS: Jurnal Pengabdian Masyarakat, 2022)
Knowledge of Mothers about IVA Test. Currently the coverage of early detection of cervical cancer is still low due to lack of information to the public about the IVA test. Efforts are needed to increase knowledge about IV tests to be able to change healthy behavior for early detection of cervical cancer. The purpose of this community service activity is to increase mother's knowledge about the VIA test. Efforts to increase knowledge about the VIA test are carried out through counseling. The target of the service is women who live in the Sindon Hamlet. The counseling materials include understanding, causes, risk factors, symptoms/signs of cervical cancer and VIA test. The material is presented in the form of Powerpoint slides and leaflets. Before the counseling began, pretest and posttest questions were given. Pretest and posttest were given to determine changes in the level of knowledge about the IVA test. Discussions and questions and answers were held after the material was delivered. The counseling was attended by 4 mothers and the implementation went well. Extension activities affect the increase in knowledge of mothers about the VIA test.